Hypoglycaemic effects of tea extracts and ent-kaurenoic acid from Smallanthus sonchifolius - Raga, Dennis D. (Animo Repository, 2010)
Hypoglycaemic activity was observed in normoglycaemic mice orally administered with the aqueous Smallanthus sonchifolius leaf tea extract, alloxan-induced diabetic mice orally administered with ent-kaurenoic acid (1), and normoglycaemic mice intraperitoneally administered with 1 from S. sonchifolius leaves. A single dose administration of 50 mg kg-1 BW yacon leaf tea extract demonstrated immediate but relatively short hypoglycaemic activity, with significant effects observed during 1-2 h. Similarly, administration with 100 mg kg-1 BW yacon leaf tea extract obtained by heavy stirring in hot water demonstrated a more potent activity compared to the positive control at 1.5-2.0 h. Oral administration of 1 did not affect the blood glucose level of the alloxan-induced diabetic mice, but a single intraperitonial injection of 10 mg kg-1 BW in normoglycaemic mice had consistent percent blood glucose reduction persisting from 1 to 2 h observation periods. © 2010 Taylor & Francis.